An Electrospinning Sample Delivery Device for Synchrotron-Based Biomacromolecule Serial Crystallography Research - Li Yu; Zhijun Wang; Qin Xu; Bo Sun; Qingjie Xiao; Weiwei Wang; Yuzhu Wang; Qisheng Wang; Jianhua He (Quantum Beam Science)
Serial crystallography is a rapidly advancing experimental technology that has seen significant development in recent years. This technique enables the continuous delivery of a series of protein crystal samples to the X-ray beam, allowing for the collection of diffraction data from a large number of crystals at ambient temperature. Despite its advancements, serial crystallography still possesses considerable potential for further development within synchrotron radiation platforms. Currently, several challenges hinder the progress of this technology, including the preparation of numerous microcrystal samples, methods for sample delivery, data acquisition efficiency, and data processing techniques. The device introduced in this paper is designed to facilitate serial crystallographic experiments at the synchrotron radiation station, employing electrospinning in the vacuum cavity to reduce the average flux, mitigate the effects of air ionization on the Taylor cone, and enhance the stability of Taylor cone during the data acquisition process. The diffraction pattern of lysozyme crystals was successfully acquired with this device at the beamlines of the Shanghai Synchrotron Radiation Facility (SSRF).